Pendidikan Islam Di Indonesia: Dari Awal Penyebaran Islam Hingga Era Reformasi Pendidikan - Novrandianti, Novi; Firdaus, Endis; Anwar, Saepul (Universitas Cokroaminoto Yogyakarta, 2024)
Islamic education is an integral part of the national education system in Indonesia, which has a long history in its development. This research aims to comprehensively explain the development of Islamic education in Indonesia from the early arrival of Islam to the present, with a focus on the dynamics and changes in each historical period. This research uses an exploratory descriptive method with a qualitative approach, where data is collected through a literature study. At the beginning of its arrival, Islam in the Archipelago spread through peaceful approaches and the integration of local values in educational and religious practices, with scholars and Sufis as the main agents of the spread of Islam. Next, the Dutch and Japanese occupations posed significant challenges to the development of Islamic education in Indonesia. After Indonesia's independence, Islamic education began to gain legitimacy with various policies issued by the government. After the reform era, Islamic education continued to develop alongside the challenges of globalization and advancements in science. This research aims to guide academics, education practitioners, and policymakers in crafting an improved and more adaptable Islamic education system to meet contemporary challenges.